2011
DOI: 10.2967/jnumed.110.083949
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in P-Glycoprotein Function in the Blood–Brain Barrier of Nonhuman Primates: PET Study with R-11C-Verapamil and 11C-Oseltamivir

Abstract: P-glycoprotein (P-gp) plays a pivotal role in limiting the penetration of xenobiotic compounds into the brain at the blood-brain barrier (BBB), where its expression increases with maturation in rats. We investigated developmental changes in P-gp function in the BBB of nonhuman primates using PET with R-11 C-verapamil, a PET radiotracer useful for evaluating P-gp function. In addition, developmental changes in the brain penetration of 11 C-oseltamivir, a substrate for P-gp, was investigated as practical example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…This negative correlation between brain distribution of oseltamivir and age-dependent P-gp expression suggests that P-gp level at the BBB is one of the determinants of brain distribution of oseltamivir. Similar results have been found in primates: P-gp level at human BBB increased with age (Daood et al, 2008) and brain distribution of 11 C-oseltamivir in infant rhesus monkeys was higher than that in adults (Takashima et al, 2011). Brain exposure to oseltamivir might be higher in human infants than in adults.…”
Section: Discussionsupporting
confidence: 80%
“…This negative correlation between brain distribution of oseltamivir and age-dependent P-gp expression suggests that P-gp level at the BBB is one of the determinants of brain distribution of oseltamivir. Similar results have been found in primates: P-gp level at human BBB increased with age (Daood et al, 2008) and brain distribution of 11 C-oseltamivir in infant rhesus monkeys was higher than that in adults (Takashima et al, 2011). Brain exposure to oseltamivir might be higher in human infants than in adults.…”
Section: Discussionsupporting
confidence: 80%
“…The mechanism by which prodrug and active metabolite could enter the brain was uncertain but, at least for Ro 64-0802, may be related to the expression of organic anion transporter 3 on both luminal and abluminal membranes of capillary endothelia. Moreover, a recent positron emission tomography study (Takashima et al, 2011) suggested that age-related developmental changes in Pgp function in the blood-brain barrier, as assessed with R-[…”
Section: Introductionmentioning
confidence: 99%
“…12) On the other hand, it has recently been reported that developmental changes in p-glycoprotein function in the blood brain barrier of rhesus monkeys using positron emission tomography (PET) with R-(11) C-oseltamivir, and this change may be closely related to the observed difference in drug responses in the brains of children and adult humans. 27) Another group, using PET and autoradiography, radioactivity observed in the brains of infant, juvenile and adult rats after injection of [(11) C] oseltamivir.…”
Section: Discussionmentioning
confidence: 99%